The "Intersubjective Turn" and the Question of Subject in Contemporary Anthropology: A Review Article - Boskovic, Aleksandar (Campos - Revista de Antropologia, 2002)
The notions related to the the self and subjectivity inspire different responses and different strategies. In his relatively recent book (Minima Ethnographica, 1999) Michael Jackson postulates a whole new theory based on the existential/phenomenological framework of relationships not only between individuals, but also between nations, peoples and various groups. The article presents a summary and an analysis of this theory, comparing it to some recent works about transcending individuality (Nigel Rapport, Transcendent Individual, 1997), as well as to some not-so-recent, but still extremely viable approaches (Mauss, Lévi-Strauss). The article points to some problems with the intersubjective turn, especially inasmuch it requires that one accepts (in advance) the whole set of philosophical premises on which it is based. But what happens when one does not accept these premises? I suggest that the notion of subjectivity could be actually a more useful one especially if limited to the actual cultural context where it is used. I also suggest that what we need more than ever in contemporary anthropology is turning our attention to the people we study and the ways in which they themselves formulate and organize the world we all live in.